Reflections of a Higher Education Leadership Coach (Journal on Excellence in College Teaching, 2024)
This article shares the insights the author has gained in coaching higher education leaders--department chairs, deans, vice presidents, and faculty--and their teams. It focuses on the attributes of higher education leadership and how the coaching process impacts these attributes; examines common areas of concern that surface during coaching, such as building trust and emotional intelligence; and looks at how individuals develop into positions of leadership and what their development means to their colleagues and their institutions. The insights offered here are attributed to the dedicated leaders with whom the author has been privileged to coach over the years.